Rye Cover Crop Impacts Soil Properties in a Long‐Term Cotton System. Issue 5 (1st September 2019) - DeLaune, P. B.; Mubvumba, P.; Lewis, K. L.; Keeling, J. W.
Abstract : Core Ideas: Soil nitrate was lower due to a cereal rye cover crop during the active growing season. Infiltration was greater for no‐till with rye cover crop than conventional tillage. After 17 years, no‐till with rye had greater soil organic C than conventional tillage in surface layers. Soil organic C did not differ between no‐till with rye and conventional tillage for subsurface layers. No‐till with rye has potential to alleviate resistance and compaction at subsurface layers. Adoption of conservation tillage in cotton cropping systems lags well behind other major crops in the United States. The Texas High Plains region is the largest cotton‐producing region in the United States and is in an area where soil and water conservation are of utmost importance. There is little information of the impacts of conservation tillage on soil function within this environment, and long‐term studies are critical to understanding potential impacts of implemented practices. As conservation tillage expands in use, understanding the impact of transitioning to such systems on nutrient cycling and soil compaction becomes paramount. Our objective was to quantify the impact of a long‐term no‐till cover crop system on soil chemical and physical properties in a continuous cotton system within a semiarid environment. Two systems implemented in 1998 were evaluated: (1) conventional tillage (CT); and (2) no‐till with a cereal rye cover crop (NT‐rye). Soil NO3 –N was significantly lower due to NT‐rye treatments during the active cover crop growing season. However, NO3 –N concentrations were not different between tillage treatments in the cotton growing season. Soil organic C (SOC) was significantly greater for NT‐rye in the upper 10 cm, and there were no significant differences for SOC between treatments to a depth of 90 cm. Bulk density and penetration resistance varied by sampling time and depth and infiltration was as much as 34% greater for NT‐rye. No‐till with a rye cover crop can increase surface SOC levels while improving infiltration and penetration resistance in semiarid continuous cotton cropping systems.